Photoionization of superheavy elements. Issue 15 (January 2020) - Khademhosseini, R; Razavi, A; Keating, D A; Deshmukh, P C; Manson, S T
Synopsis: Calculations of the photoionization cross sections for the superheavy atoms of atomic numbers 102, 112 and 118 have been performed using the relativistic-random-phase approximation (RRPA) which is based on the Dirac equation. The results show that relativistic effects cause anomalies in level ordering for some inner shells, and that interchannel coupling is of great importance.